Exploring the role of inhaled corticosteroid/betamethasone for managing recurrent respiratory illness in infants and young children - Dutta, Arup; Newaz, Taslima; Purba, Srobonti Dutta; Day, Arpon; Kamal, S. M. Zahed; Alam, Mohammad Toufiq Ul (International Journal of Contemporary Pediatrics, 2024)
Background: Recurrent respiratory illnesses (RRIs) are frequent respiratory tract infections, particularly common in fall-winter and during seasonal changes. RRIs primarily affect children aged 2-7 years and the elderly, with respiratory viruses causing about 80% of cases. They interfere significantly with children's well-being and incur substantial medical and social costs. The study aim was to assess the effectiveness of inhaled corticosteroids (ICS) in infants and young children with recurrent respiratory symptoms. Methods: This prospective observational study took place over one year at the department of pediatrics, Cox’s Bazar medical college, Bangladesh, from June 1, 2014, to May 31, 2015. Results: The study involved 210 children with recurrent respiratory symptoms, mostly males (57.62%) and predominantly aged 1-3 years (55.71%). Atopy was present in 16.67%, and eczema in 30.48%. Only 2.38% of mothers smoked during pregnancy, and 20.48% of children were exposed to passive smoke. Salbutamol use was high (80.48%), and 32.86% used ICS. Symptoms ranged from mild (13.81%) to severe (23.81%). After six months, daytime cough reduced from 52.38% to 1.43%, and nighttime cough from 66.19% to 0%. Symptom-free days increased, and hospital admissions decreased from 90.95% to 9.05%. Common adverse events included worsening symptoms (13.81%) and fever (13.33%). Conclusions: Inhaled corticosteroid/betamethasone therapy significantly improved symptoms in infants and young children with RRIs over six months, reducing coughing, wheezing, shortness of breath, and hospital admissions, while increasing symptom-free days. Adverse events were mild and infrequent, suggesting ICS is effective and safe. Further research is needed to optimize treatment.